The determinants of cash waqf re-endow intention in Malaysia - Marina Kassim; Nor Azizan Che Embi; Razali Haron; Khairunisah Ibrahim (al-Uqud : Journal of Islamic Economics, 2023)
Cash waqf has significant potential to improve Muslims' economies, particularly in financing social and cultural activities. Most governments today are experiencing financial difficulties, with inadequate means to cover public needs and ensure that all residents are in good standing. Thus, this paper discusses internal factors such as trust, familiarity, and perceived efficacy as possible factors influencing cash waqf endowers' intention to reendow. The population for this study is 13,940 cash waqf donors in the Klang Valley, which covers Selangor and Kuala Lumpur, and a purposive sampling method was used. Based on the finding gathered using PLS analysis on 382 respondents indicated that internal factors (trust, familiarity, perceived efficacy) positively influence intention to reendow among cash waqf endowers. Trust is the most dominant factor that influences the intention to reendow. It may indicate that the higher the trust level a person has, the higher the intention to reendow. These study suggestions are other variables influencing the intention to reendow and should be explored further. Moreover, this study offers management implications, such as empirically proven conclusions on internal factors (trust, familiarity, perceived efficacy) that influence endowers' intention to reendow to waqf organisations.